Lifestyle Factors of Low Birth Weight: Evidence from the 2023 Indonesian Health Survey - Marhadi, Nancy; Anisah, Zhafirah Yanzli; Saputro, Widiantoro (BPJS Kesehatan, 2025)
The stagnant prevalence of low birth weight (LBW) in Indonesia creates challenges for the National Health Insurance (Jaminan Kesehatan Nasional/JKN), as it often needs more medical care with higher inpatient claim costs and affects the long-term growth and development of the country’s future generations. The objective of this study was to identify significant maternal lifestyle factors associated with LBW by analyzing the data from the Indonesian Health Survey (SKI) 2023. A total of 30,516 mothers who had given birth at least once during the five-year period preceding the SKI 2023 were included in the study. Bivariate and multivariable logistic regression analyses were used to identify key maternal factors associated with the outcome. Living in urban areas (AOR: 1.228; 95% CI: 1.038–1.453), exposure to second-hand smoke (AOR: 1.383; 95% CI: 1.149–1.664), infrequent consumption of energy drinks (AOR: 2.501; 95% CI: 1.015–6.161), and frequent vegetable consumption (AOR: 1.217; 95% CI: 1.030–1.437) were significant contributors. Additionally, the effect of low-frequency instant food consumption was more pronounced among mothers with only primary education (AOR: 4.740; 95% CI: 1.438–15.623). To lower LBW rates, healthcare providers should focus on educating expectant mothers about the risks of second-hand smoke and unbalanced nutrition through quality antenatal care.